Answer:
![x = 2 \pm \frac12\sqrt7](https://img.qammunity.org/2023/formulas/mathematics/high-school/n9yd2o07ekro9bcg97mart33fyzunysm5b.png)
Explanation:
Hello!
Expand the left-hand side of the equation:
- (2x - 3)²
- (2x-3)(2x-3)
- (2x-3)(2x) +(2x-3)(-3)
- 4x² - 6x - 6x + 9
- 4x² - 12x + 9
Create the Equation:
- 4x² - 12x + 9 = 4x
- 4x² - 16x + 9 = 0
Solve using the quadratic formula:
The roots of the equation are
![x = 2 \pm \frac12\sqrt7](https://img.qammunity.org/2023/formulas/mathematics/high-school/n9yd2o07ekro9bcg97mart33fyzunysm5b.png)